Kocuria tytonicola, new bacteria from the preen glands of American barn owls (Tyto furcata) - Braun, Markus S.; Wang, Erjia; Zimmermann, Stefan; Boutin, Sébastien; Wink, Michael (Systematic and applied microbiology, 2019)
Although birds are hosts to a large number of microorganisms, microbes have rarely been found in avian oil glands. Here, we report on two strains of a new bacterial species from the preen oil of American barn owls (Tyto furcata). Phenotypic as well as genotypic methods placed the isolates to the genus Kocuria. Strains are non-fastidious, non-lipophilic Gram-positive cocci and can be unambiguously discriminated from their closest relative Kocuria rhizophila DSM 11926T. In phylogenetic trees, the owl bacteria formed a distinct cluster which was clearly separated from all other known Kocuria species. The same conclusion was drawn from MALDI-TOF MS analyses. Once again, the new bacterial strains were very similar to one another, but exhibited substantial differences when compared to the most closely related species. Besides, the results of the biochemical tests, optimum growth conditions and pigmentation differed from closely related Kocuria spp. Finally, ANIb values of less than 87% provided striking evidence that the isolates recovered from American barn owls represent a hitherto undescribed species, for which we propose the name Kocuria tytonicola sp. nov. The type strain is 489T (DSM 104133T=LMG 29945T, taxonumber TA00340).